Kewajiban Pekerja Dalam Menerapkan Employee Branding: Perspektif Hukum dan Praktik Perusahaan - Ellya Rosa; Mega Dewi Ambarwati (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Employee branding is an important strategy for companies in building a positive image in the eyes of employees, customers, and the public. This strategy aims to create alignment between company values and employee behavior, so that it can increase the company's competitiveness. Although the main responsibility for building employee branding usually lies with the company, workers also have a significant role and obligation to support the success of the process. This article examines workers' obligations within the framework of Indonesian labor law, including relevant laws and regulations, such as Article 1330 of the Civil Code, which regulates workers' legal capacity to make employment agreements. This study also explores how companies can integrate employee branding into their work policies and culture through employee training, incentives, and development programs. In addition, this article discusses the implementation practices of employee branding in various companies and the challenges faced in ensuring worker compliance with company values. This study aims to provide in-depth insight into the importance of collaboration between companies and workers in creating effective and sustainable employee branding. With this understanding, it is hoped that companies and workers can work together to build harmonious working relationships while supporting business sustainability. This article contributes to the literature on employment law and human resource management strategies in Indonesia.